2012
DOI: 10.1353/hpu.2012.0070
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Tailored Health Camps and Cardiovascular Risk among South Asian Immigrants

Abstract: Health camps are a potentially important component in addressing increased CVD risk in this vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Multi-lingual outreach staff surveyed participants using an intake questionnaire that had been used by the researchers in prior health fair events. 46 Questions regarding demographics, employment, healthcare access, medical history, tobacco use, physical activity (derived from the National Health and Nutrition Examination Survey Questionnaire 49 ) and migration were included. Height (using a measuring tape affixed to a fence), weight (using a Taylor 7009 Lithium Electronic Scale), and waist circumference (measured by placing a tape measure snugly and parallel to the floor on the participant's abdomen just above the hip bone) were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Multi-lingual outreach staff surveyed participants using an intake questionnaire that had been used by the researchers in prior health fair events. 46 Questions regarding demographics, employment, healthcare access, medical history, tobacco use, physical activity (derived from the National Health and Nutrition Examination Survey Questionnaire 49 ) and migration were included. Height (using a measuring tape affixed to a fence), weight (using a Taylor 7009 Lithium Electronic Scale), and waist circumference (measured by placing a tape measure snugly and parallel to the floor on the participant's abdomen just above the hip bone) were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…Inclusion of these variables for assessment was informed by the authors' prior work addressing the health concerns of drivers. 1,46 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…WC was measured at the midpoint point between the iliac crest and lower rib to the nearest 0·1 cm. The cut-off values for WC were ≥90 cm in males, ≥80 cm in females ( 6 ) .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…MetS studies of SA in the Asian subcontinent have shown increased prevalence compared with Americans ( 4 , 5 ) . In the USA, low-income SA populations have a greater prevalence of obesity and related diseases ( 6 , 7 ) , have less access to healthful foods, less physical activity outlets and generally less knowledge related to health management ( 4 , 5 ) . Physiological and metabolic markers of low-income immigrant populations associated with MetS can be assessed in community health clinics.…”
mentioning
confidence: 99%